The effects of different exercise types on visuospatial attention in the elderly. (September 2016) - Tsai, Chia-Liang; Wang, Chun-Hao; Pan, Chien-Yu; Chen, Fu-Chen; Huang, Shu-Yu; Tseng, Yu-Ting
Abstract: While the capability of visuospatial attention decreases with advanced aging, exercise is an effective primary prevention strategy to ward off the progression of such cognitive declines among the elderly. However, no studies have yet been conducted on the relationship between exercise type and visuospatial attention in the elderly. This study was thus carried out to explore the effects of open- and closed-skill exercise modes on visuospatial attention in the elderly using behavioral and cognitive electrophysiological measurements. Sixty elderly participants were divided into open-skill (n = 20), closed-skill (n = 20), or control (n = 20) groups according to their exercise-participation experience in the previous 24 months, and performed a visuospatial attention task with concomitant electrophysiological recording. The results showed that the two exercise groups (i.e., open- and closed-skill) exhibited shorter reaction times (RTs) and larger P3 amplitudes across conditions compared with the control group. Although the open- and closed-skill groups only showed approaching between-group significance on the RTs in the invalid condition and on the P3 amplitudes across conditions, only the open-skill group showed better inhibitory control of attention relative to the control group. These findings reveal the presence of neurocognitive effects on the visuospatial attention task in the two exercise groups, with significantly better performances in the open-skill group, demonstrating that regularly participating in such an exercise mode, as compared to the closed-skill one, could have more beneficial effects on visuospatial attention. Highlights: Different exercise types could have unique effects on cognitive performance. Open-skill exercise has more beneficial effects on the visuospatial attention. Greater aerobic fitness improves neurocognitive performances for the elderly. A physically active lifestyle is very important for the elderly.